Pengetahuan dengan Motivasi Wanita Usia Subur (WUS) tentang Vulva Hygienen terhadap Pencegahan Keputihan - Tri Ardayani (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the relationship between the knowledge and motivation of women of childbearing age regarding vulva hygiene to prevent leucorrhoea. The method used is quantitative with a cross-sectional research design. The sampling technique was done using simple random sampling and data analysis using the chi-square test. The results showed that many women of childbearing age experienced leucorrhoea, knowledge was relatively low and motivation was low. In conclusion, there is no significant relationship between the knowledge and motivation of women of childbearing age about vulva hygiene to prevent leucorrhoea. Keywords: Leucorrhoea, Vulva Hygiene, Women of Reproductive Age